OCULAR SURFACE TEMPERATURE DIFFERENCES IN RETINAL VASCULAR DISEASES - Naidorf-Rosenblatt, Hadar; Landau-Part, Daphna; Moisseiev, Joseph; Alhalel, Amir; Huna-Baron, Ruth; Skaat, Alon; Pilus, Sima; Levi, Lior; Leshno, Ari (Retina (Philadelphia, Pa.), 2022)
To define the effect of age-related macular degeneration (AMD) and diabetic retinopathy (DR) on the ocular thermographic profile. This retrospective cross-sectional study included subjects diagnosed with DR or AMD between January and April 2019. Individuals without ocular disease served as controls. A thermal imaging camera was used for ocular surface temperature (OST) acquisition. The mean temperatures of the medial cantus, lateral cantus, and cornea were calculated. Thermographic images were obtained from 133 subjects (260 eyes, 97 DR and 163 AMD) and 48 controls (55 eyes). Ocular surface temperature was higher among patients with AMD and lowest among patients with DR (P < 0.001). A subgroup analysis revealed that eyes with diabetic macular edema had significantly higher OSTs than DR eyes without diabetic macular edema. Moreover, the OST in eyes with diabetic macular edema was similar to the measurements of the AMD group. There were no differences in OSTs between neovascular and nonneovascular AMD eyes. Although AMD and DR are considered posterior segment conditions, their effect on OST implies that the entire globe is involved. Although both conditions result from similar multifactorial pathophysiologic changes, the differences in OST between DR and AMD might be due to dissimilarity in the balance of pathologic processes involved in each condition. Further research is required to better understand the pathophysiology of these diseases and their effect on OST as well as to determine the effect of vasculature, circulation, and tissue metabolism on ocular temperature.